1985
DOI: 10.1021/np50039a009
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Erysimum inconspicuum. Two Sulfur-Containing Lactone Compounds

Abstract: The alcohol extract of Erysimum inconspicuum fruits, which exhibited cytotoxic activity against the KB cell line and some activity against the P-388 lymphocytic leukemia in vivo, was studied. Strophanthidin, uzarigenin, and two sulfur-containing lactones, erysulfone[6-methylsulfonyl-4-hydroxyhexanoic acid lactone] and erysulfoxide[6-methylsulfinyl-4-hydroxyhexanoic acid lactone], were isolated and characterized by spectral data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…We observed substantial interspecific variation in the accumulation of 5α-, 5β-, and dehydro-cardenolides across the Erysimum genus. Although cardenolides of each type had been reported previously in at least one Erysimum species (22, 24, 50), other studies focused primarily on 5β-cardenolides (45, 51). We found that the 5β-cardenolides digitoxigenin and cannogenin were restricted to a monophyletic clade containing E. cheiranthoides , E. sylvestre , and two closely related species of uncertain taxonomic identity (43), and that their occurrence coincided with expression of a functional P5βR2-1 .…”
Section: Discussionmentioning
confidence: 99%
“…We observed substantial interspecific variation in the accumulation of 5α-, 5β-, and dehydro-cardenolides across the Erysimum genus. Although cardenolides of each type had been reported previously in at least one Erysimum species (22, 24, 50), other studies focused primarily on 5β-cardenolides (45, 51). We found that the 5β-cardenolides digitoxigenin and cannogenin were restricted to a monophyletic clade containing E. cheiranthoides , E. sylvestre , and two closely related species of uncertain taxonomic identity (43), and that their occurrence coincided with expression of a functional P5βR2-1 .…”
Section: Discussionmentioning
confidence: 99%